IMPACTO DAS MUDANÇAS CLIMÁTICAS NAS FLORESTAS RIPÁRIAS DA BACIA DO ALTO PARAGUAI - Gabriel Andreio Cabrera, Pedro; Henrique Silvestre Cardinal , Renan; Gabriela da Silva Motto , Maria; Fernanda de Oliveira, Samara; Vieira , Eliane; Leandro Bueno, Marcelo (ANAIS DO ENIC, 2026)
-